Solid gum applied to mirror and preparation method of solid gum

By combining acrylic resin, sulfur-containing polyurethane, fluorine-modified sulfaguanidine, epoxy nano-silica and other materials, mirror solid glue with flame retardant, antibacterial and self-cleaning functions is prepared, which solves the problem of the solid glue in the prior art The problems of bacterial erosion and insufficient antibacterial performance improve their performance and stability.

CN119242220AInactive Publication Date: 2025-01-03LINYI JINGXIN MIRROR IND CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411773870.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing mirror solid glue is susceptible to bacterial erosion during long-term use, resulting in degradation of performance and insufficient antibacterial performance.

Method used

Flame-retardant, antibacterial and self-cleaning solid glue is formed by a specific preparation method using a combination of acrylic resin, sulfur-containing polyurethane, fluorine-modified sulfaguanidine, epoxy nanosilica, polyvinylpyrrolidone, glycerol and deionized water.

Benefits of technology

The flame retardant, antibacterial and self-cleaning effects of solid glue are achieved, and its mechanical properties and use stability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of solid gum, and discloses solid gum applied to a mirror and a preparation method thereof.The solid gum applied to the mirror is obtained by adding acrylic resin, sulfur-containing polyurethane, fluorine-modified sulfaguanidine, epoxy nano-silica, polyvinylpyrrolidone, glycerol and deionized water into a stirrer and stirring. A sulfur element, a phosphorus element, guanidyl and a sulfur element in the sulfur-containing polyurethane and the fluorine-modified sulfaguanidine have a relatively good flame-retardant effect and jointly form a flame-retardant system; a quaternary ammonium salt group contained in the antibacterial agent has a relatively good antibacterial effect; the fluorine element in the solid gum can enable the surface of the solid gum to form a smooth fluorine carbonization layer which is not easy to attach with an object, so that the solid gum also has a better self-cleaning effect; and meanwhile, the material also has better mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solid glue, in particular to a solid glue applied to mirrors and a preparation method thereof. Background Art

[0002] Solid glue for mirrors usually refers to the adhesive used to fix the mirror on the wall, frame or other supports. However, during long-term use, it will be corroded by bacteria, resulting in poor performance, thus affecting its normal use. For example, patent CN118308044A discloses a solid glue stick and its preparation method. The solid glue stick of the invention oxidizes starch to improve its storage stability and adhesion, uses enzyme-catalyzed oxidation to prepare oxidized starch, adds sucrose and degradable aqueous polymer material polyvinyl alcohol, is safe and environmentally friendly, and the obtained solid glue has strong adhesion, is easy to make, and is highly practical; however, its antibacterial performance is not improved. Summary of the invention

[0003] 1. Technical issues to be resolved In view of the deficiencies in the prior art, the present invention provides a solid glue for mirrors and a preparation method thereof, which has good flame retardant, antibacterial, stretchable and self-cleaning effects.

[0004] (II) Technical solution To achieve the above object, the present invention provides the following technical solution: a solid glue for mirrors, comprising the following components by weight: 13-18 parts by weight of acrylic resin, 5-9 parts by weight of sulfur-containing polyurethane, 2-6 parts by weight of fluorine-modified sulfaguanidine, 1-2 parts by weight of epoxy nano-silica, 3-5 parts by weight of polyvinyl pyrrolidone, 2-4 parts by weight of glycerol, and 10-12 parts by weight of deionized water; The preparation method of the sulfur-containing polyurethane is: (1) adding sulfaguanidine to anhydrous ethanol solvent, stirring and mixing, heating to 70-90°C to completely dissolve it, then continuing to add p-dimethylaminobenzaldehyde, stirring and reacting for 10-15 hours, then adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, stirring and reacting at 75-85°C for 6-10 hours, and washing with anhydrous ethanol and deionized water 2-3 times each after completion, and drying to obtain modified sulfaguanidine; (2) adding modified sulfaguanidine and 3-chloropropylene to N,N-dimethylformamide solvent, stirring and dissolving, and carrying out quaternization reaction at 60-80°C for 7-15h. After the reaction, distilling under reduced pressure, washing and drying are performed to obtain alkenyl-modified sulfaguanidine; (3) Add 2-aminoethanethiol, alkenyl-modified sulfaguanidine and dimethylphenylphosphine to the dimethyl sulfoxide solvent, stir and mix, introduce nitrogen protection, heat to 65-85°C, apply mechanical stirring at 115-120 rpm, 300-310 W / m 2 UV irradiation, stirring and reacting for 2-5 hours, after completion, vacuum rotary evaporation to remove the solvent, washing, and drying to obtain a quaternary ammonium salt chain extender; (4) After removing water from the polyether diol, mix it evenly with hexamethylene diisocyanate, introduce nitrogen, then add dibutyltin dilaurate as a catalyst dropwise, react at 50-75°C for 3-5 hours to carry out prepolymerization, then add a quaternary ammonium salt chain extender, stir to continue the chain extension reaction, react at 40-70°C for 2-3 hours, and after the reaction is completed, cool and discharge to obtain a sulfur-containing polyurethane.

[0005] Preferably, the mass ratio of sulfaguanidine, p-dimethylaminobenzaldehyde and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in (1) is 1:1.6-3.4:1.3-1.8.

[0006] Preferably, the mass ratio of modified sulfaguanidine to 3-chloropropylene in (2) is 0.4-0.6:1.

[0007] Preferably, the mass ratio of 2-aminoethanethiol, alkenyl-modified sulfaguanidine and dimethylphenylphosphine in (3) is 2.3-2.7:1:0.01-0.03.

[0008] Preferably, the mass ratio of the polyether diol after dehydration, hexamethylene diisocyanate, dibutyltin dilaurate catalyst, and quaternary ammonium salt chain extender in (4) is 1.1-2.3:1:0.01-0.03:0.4-0.6.

[0009] Preferably, the preparation method of the fluorine-modified sulfaguanidine is: perfluorooctanoyl chloride and a quaternary ammonium salt chain extender are added to a tetrahydrofuran solvent, and then a triethylamine catalyst is added thereto, and the reaction is carried out at 75-100° C. for 4-6 hours. After the reaction is completed, the solvent is removed by reduced pressure distillation, and the fluorine-modified sulfaguanidine is washed and recrystallized to obtain the fluorine-modified sulfaguanidine.

[0010] Preferably, the mass ratio of perfluorooctanoyl chloride, quaternary ammonium salt chain extender and triethylamine catalyst is 0.4-0.51:1:0.02-0.03.

[0011] Preferably, the preparation method of the solid glue applied to the mirror is: adding acrylic resin, sulfur-containing polyurethane, fluorine-modified sulfaguanidine, epoxy nano-silica, polyvinyl pyrrolidone, glycerol, and deionized water into a stirrer, stirring at 60-75° C. for 10-15 minutes to obtain the solid glue applied to the mirror.

[0012] 3. Beneficial technical effects The invention prepares solid glue for mirrors by adding acrylic resin, sulfur-containing polyurethane, fluorine-modified sulfaguanidine, epoxy nano-silicon dioxide, polyvinyl pyrrolidone, glycerol and deionized water into a stirrer and stirring the mixture.

[0013] The sulfur, phosphorus, guanidine and sulfur elements in sulfur-containing polyurethane and fluorine-modified sulfaguanidine have good flame retardant effects and together constitute a flame retardant system; the quaternary ammonium salt groups contained therein have good antibacterial effects; the fluorine element in the solid glue can form a smooth fluorinated carbonized layer on its surface that is not easy to adhere to objects, so it also has a good self-cleaning effect. During the stirring process, the epoxy groups in the epoxy nano-silica will undergo a ring-opening reaction with the terminal hydroxyl groups in the sulfur-containing polyurethane to generate new hydroxyl groups, which will further form hydrogen bonds with the fluorine elements in the fluorine-modified sulfaguanidine, increasing the compatibility between the three, and forming a tight cross-linked network, improving its mechanical properties. DETAILED DESCRIPTION

[0014] Example 1 (1) adding sulfaguanidine to anhydrous ethanol solvent, stirring and mixing, heating to 70°C to completely dissolve it, then continuing to add p-dimethylaminobenzaldehyde, stirring and reacting for 10 hours, and then adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, wherein the mass ratio of sulfaguanidine, p-dimethylaminobenzaldehyde and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:1.6:1.3, stirring and reacting at 75°C for 6 hours, and washing with anhydrous ethanol and deionized water twice each after completion, and drying to obtain modified sulfaguanidine; (2) adding modified sulfaguanidine and 3-chloropropylene to N,N-dimethylformamide solvent, wherein the mass ratio of modified sulfaguanidine to 3-chloropropylene is 0.4:1, stirring and dissolving, and performing quaternization reaction at 60° C. for 7 h. After completion, performing reduced pressure distillation, washing and drying to obtain alkenyl-modified sulfaguanidine; (3) Add 2-aminoethanethiol, alkenyl-modified sulfaguanidine and dimethylphenylphosphine to dimethyl sulfoxide solvent, wherein the mass ratio of 2-aminoethanethiol, alkenyl-modified sulfaguanidine and dimethylphenylphosphine is 2.3:1:0.01, stir and mix, introduce nitrogen protection, heat to 65°C, apply mechanical stirring at 115 rpm, and 300 W / m 2 UV irradiation, stirring and reacting for 2 hours, after which the solvent is removed by vacuum rotary evaporation, washing and drying to obtain a quaternary ammonium salt chain extender; (4) The dehydrated polyether diol is mixed with hexamethylene diisocyanate, nitrogen is introduced, and then dibutyltin dilaurate catalyst is added dropwise, and the mixture is reacted at 50°C for 3 hours for prepolymerization, and then a quaternary ammonium salt chain extender is added, wherein the mass ratio of the dehydrated polyether diol, hexamethylene diisocyanate, dibutyltin dilaurate catalyst, and quaternary ammonium salt chain extender is 1.1:1:0.01:0.4, and the chain extension reaction is continued by stirring, and the mixture is reacted at 40°C for 2 hours. After the reaction is completed, the mixture is cooled and discharged to obtain a sulfur-containing polyurethane; (5) adding perfluorooctanoyl chloride and a quaternary ammonium salt chain extender to a tetrahydrofuran solvent, and then continuing to add a triethylamine catalyst thereto, wherein the mass ratio of perfluorooctanoyl chloride, the quaternary ammonium salt chain extender, and the triethylamine catalyst is 0.4:1:0.02, reacting at 75° C. for 4 hours, and after the reaction is completed, removing the solvent by reduced pressure distillation, washing, and recrystallizing to obtain a fluorinated modified sulfaguanidine; (6) Add 13 parts by weight of acrylic resin, 5 parts by weight of sulfur-containing polyurethane, 2 parts by weight of fluorine-modified sulfaguanidine, 1 part by weight of epoxy nanosilica, 3 parts by weight of polyvinyl pyrrolidone, 2 parts by weight of propylene glycol, and 10 parts by weight of deionized water into a stirrer, and stir at 60° C. for 10 minutes to obtain a solid glue for use on a mirror.

[0015] Example 2 (1) adding sulfaguanidine to anhydrous ethanol solvent, stirring and mixing, heating to 90°C to completely dissolve it, then continuing to add p-dimethylaminobenzaldehyde, stirring and reacting for 15 hours, and then adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, wherein the mass ratio of sulfaguanidine, p-dimethylaminobenzaldehyde and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:3.4:1.8, stirring and reacting at 85°C for 10 hours, and washing with anhydrous ethanol and deionized water for 3 times each after completion, and drying to obtain modified sulfaguanidine; (2) adding modified sulfaguanidine and 3-chloropropylene to N,N-dimethylformamide solvent, wherein the mass ratio of modified sulfaguanidine to 3-chloropropylene is 0.6:1, stirring and dissolving, and carrying out quaternization reaction at 80° C. for 15 h. After the reaction, distilling under reduced pressure, washing and drying are carried out to obtain alkenyl-modified sulfaguanidine; (3) Add 2-aminoethanethiol, alkenyl-modified sulfaguanidine and dimethylphenylphosphine to dimethyl sulfoxide solvent, wherein the mass ratio of 2-aminoethanethiol, alkenyl-modified sulfaguanidine and dimethylphenylphosphine is 2.7:1:0.03, stir and mix, introduce nitrogen protection, heat to 85°C, apply mechanical stirring at 120 rpm, 310 W / m 2 UV irradiation, stirring and reacting for 5 hours, after which the solvent is removed by vacuum rotary evaporation, washing and drying to obtain a quaternary ammonium salt chain extender; (4) The dehydrated polyether diol is mixed with hexamethylene diisocyanate, nitrogen is introduced, and then dibutyltin dilaurate catalyst is added dropwise, and the mixture is reacted at 75°C for 5 hours for prepolymerization, and then a quaternary ammonium salt chain extender is added, wherein the mass ratio of the dehydrated polyether diol, hexamethylene diisocyanate, dibutyltin dilaurate catalyst, and quaternary ammonium salt chain extender is 2.3:1:0.03:0.6, and the chain extension reaction is continued by stirring, and the mixture is reacted at 70°C for 3 hours. After the reaction is completed, the mixture is cooled and discharged to obtain a sulfur-containing polyurethane; (5) adding perfluorooctanoyl chloride and a quaternary ammonium salt chain extender to a tetrahydrofuran solvent, and then continuing to add a triethylamine catalyst thereto, wherein the mass ratio of perfluorooctanoyl chloride, the quaternary ammonium salt chain extender, and the triethylamine catalyst is 0.51:1:0.03, reacting at 100° C. for 6 hours, and after the reaction is completed, removing the solvent by reduced pressure distillation, washing, and recrystallizing to obtain a fluorine-modified sulfaguanidine; (6) Add 18 parts by weight of acrylic resin, 9 parts by weight of sulfur-containing polyurethane, 6 parts by weight of fluorine-modified sulfaguanidine, 2 parts by weight of epoxy nanosilica, 5 parts by weight of polyvinyl pyrrolidone, 4 parts by weight of glycerol, and 12 parts by weight of deionized water into a stirrer, and stir at 75° C. for 15 minutes to obtain a solid glue for use on a mirror.

[0016] Example 3 (1) adding sulfaguanidine to anhydrous ethanol solvent, stirring and mixing, heating to 80°C to completely dissolve it, then continuing to add p-dimethylaminobenzaldehyde, stirring and reacting for 12 hours, and then adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, wherein the mass ratio of sulfaguanidine, p-dimethylaminobenzaldehyde and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:3.2:1.5, stirring and reacting at 80°C for 8 hours, and washing with anhydrous ethanol and deionized water twice each after completion, and drying to obtain modified sulfaguanidine; (2) adding modified sulfaguanidine and 3-chloropropylene to N,N-dimethylformamide solvent, wherein the mass ratio of modified sulfaguanidine to 3-chloropropylene is 0.5:1, stirring and dissolving, and performing quaternization reaction at 70°C for 10 hours. After the reaction, performing reduced pressure distillation, washing and drying to obtain alkenyl-modified sulfaguanidine; (3) Add 2-aminoethanethiol, alkenyl-modified sulfaguanidine and dimethylphenylphosphine to dimethyl sulfoxide solvent, wherein the mass ratio of 2-aminoethanethiol, alkenyl-modified sulfaguanidine and dimethylphenylphosphine is 2.5:1:0.02, stir and mix, introduce nitrogen protection, heat to 75°C, apply mechanical stirring at 118 rpm, 308 W / m 2 UV irradiation, stirring and reacting for 4 hours, after which the solvent is removed by vacuum rotary evaporation, washing and drying to obtain a quaternary ammonium salt chain extender; (4) The dehydrated polyether diol is mixed with hexamethylene diisocyanate, nitrogen is introduced, and then dibutyltin dilaurate catalyst is added dropwise, and the mixture is reacted at 65°C for 4 hours for prepolymerization, and then a quaternary ammonium salt chain extender is added, wherein the mass ratio of the dehydrated polyether diol, hexamethylene diisocyanate, dibutyltin dilaurate catalyst, and quaternary ammonium salt chain extender is 1.8:1:0.02:0.5, and the chain extension reaction is continued by stirring at 50°C for 2.5 hours. After the reaction is completed, the mixture is cooled and discharged to obtain a sulfur-containing polyurethane; (5) adding perfluorooctanoyl chloride and a quaternary ammonium salt chain extender to a tetrahydrofuran solvent, and then continuing to add a triethylamine catalyst thereto, wherein the mass ratio of perfluorooctanoyl chloride, the quaternary ammonium salt chain extender, and the triethylamine catalyst is 0.4:1:0.03, reacting at 100° C. for 5 h, and after the reaction is completed, removing the solvent by reduced pressure distillation, washing, and recrystallizing to obtain a fluorine-modified sulfaguanidine; (6) Add 15 parts by weight of acrylic resin, 7 parts by weight of sulfur-containing polyurethane, 4 parts by weight of fluorine-modified sulfaguanidine, 1 part by weight of epoxy nanosilica, 5 parts by weight of polyvinyl pyrrolidone, 3 parts by weight of propylene glycol, and 11 parts by weight of deionized water into a stirrer, and stir at 65° C. for 12 minutes to obtain a solid glue for use on a mirror.

[0017] Example 4 (1) adding sulfaguanidine to anhydrous ethanol solvent, stirring and mixing, heating to 70°C to completely dissolve it, then continuing to add p-dimethylaminobenzaldehyde, stirring and reacting for 10 hours, and then adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, wherein the mass ratio of sulfaguanidine, p-dimethylaminobenzaldehyde and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 1:1.6:1.3, stirring and reacting at 75°C for 6 hours, and washing with anhydrous ethanol and deionized water twice each after completion, and drying to obtain modified sulfaguanidine; (2) adding modified sulfaguanidine and 3-chloropropylene to N,N-dimethylformamide solvent, wherein the mass ratio of modified sulfaguanidine to 3-chloropropylene is 0.4:1, stirring and dissolving, and performing quaternization reaction at 60° C. for 7 h. After completion, performing reduced pressure distillation, washing and drying to obtain alkenyl-modified sulfaguanidine; (3) Add 2-aminoethanethiol, alkenyl-modified sulfaguanidine and dimethylphenylphosphine to dimethyl sulfoxide solvent, wherein the mass ratio of 2-aminoethanethiol, alkenyl-modified sulfaguanidine and dimethylphenylphosphine is 2.7:1:0.03, stir and mix, introduce nitrogen protection, heat to 85°C, apply mechanical stirring at 120 rpm, 310 W / m 2 UV irradiation, stirring and reacting for 5 hours, after which the solvent is removed by vacuum rotary evaporation, washing and drying to obtain a quaternary ammonium salt chain extender; (4) The dehydrated polyether diol is mixed with hexamethylene diisocyanate, nitrogen is introduced, and then dibutyltin dilaurate catalyst is added dropwise, and the mixture is reacted at 75°C for 5 hours for prepolymerization, and then a quaternary ammonium salt chain extender is added, wherein the mass ratio of the dehydrated polyether diol, hexamethylene diisocyanate, dibutyltin dilaurate catalyst, and quaternary ammonium salt chain extender is 2.3:1:0.03:0.6, and the chain extension reaction is continued by stirring, and the mixture is reacted at 70°C for 3 hours. After the reaction is completed, the mixture is cooled and discharged to obtain a sulfur-containing polyurethane; (5) adding perfluorooctanoyl chloride and a quaternary ammonium salt chain extender to a tetrahydrofuran solvent, and then continuing to add a triethylamine catalyst thereto, wherein the mass ratio of perfluorooctanoyl chloride, the quaternary ammonium salt chain extender, and the triethylamine catalyst is 0.4:1:0.03, reacting at 100° C. for 5 h, and after the reaction is completed, removing the solvent by reduced pressure distillation, washing, and recrystallizing to obtain a fluorine-modified sulfaguanidine; (6) Add 15 parts by weight of acrylic resin, 7 parts by weight of sulfur-containing polyurethane, 4 parts by weight of fluorine-modified sulfaguanidine, 1 part by weight of epoxy nanosilica, 5 parts by weight of polyvinyl pyrrolidone, 3 parts by weight of propylene glycol, and 11 parts by weight of deionized water into a stirrer, and stir at 65° C. for 12 minutes to obtain a solid glue for use on a mirror.

[0018] Comparative Example 1 Compared with Example 5, the difference in this comparative example is that no sulfur-containing polyurethane is added.

[0019] Comparative Example 2 Compared with Example 5, this comparative example is different in that no fluorine-modified sulfaguanidine is added.

[0020] The oxygen index meter was used to test the limiting oxygen index of the coating, and the horizontal and vertical combustion instrument was used to test the combustion grade of the coating. The test results are shown in Table 1.

[0021] Table 1: Flame retardancy tests.

[0022]

[0023] It can be seen from Table 1 that Examples 1-4 of the present invention have better flame retardant effects than Comparative Examples 1-2.

[0024] Pipette 1 mL of 10 8 CFU / mL of Staphylococcus aureus was added to PBS buffer, and then diluted 10-fold to 10 5CFU / mL, then add solid gel sample (1 cm×1cm×0.2cm), and then culture in a constant temperature incubator at 37℃ with shaking for 24 h. After culture, add PBS buffer to dilute the bacterial solution 10 times in sequence, and then transfer 0.5 mL of the bacterial solution to the agar medium, and continue to culture at 37℃ with shaking for 24 h. After culture, count the colonies and count the antibacterial rate.

[0025] Table 2: Antibacterial performance test.

[0026]

[0027] It can be seen from Table 2 that Examples 1-4 of the present invention have better antibacterial effects than Comparative Examples 1-2.

[0028] The mechanical properties of the solid glue were tested using a universal electronic testing machine with a tensile rate of 100 mm / min. The test results are shown in Table 3.

[0029] Table 3: Tensile properties tested.

[0030]

[0031] It can be seen from Table 3 that Examples 1-4 of the present invention have better stretching effects than Comparative Examples 1-2.

[0032] The solid gels of Examples 1-4 and Comparative Examples 1-2 were characterized for surface wettability and contact angle tests according to JC2000D.

[0033] Table 4: Contact angle test.

[0034]

[0035] As can be seen from Table 4, compared with Comparative Example 1-2, the contact angle of Example 1-4 is larger, resulting in the water droplet being unable to spread and being very easy to slide, indicating that the solid glue prepared by the present invention has a good self-cleaning function.

[0036] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A solid glue for mirrors, characterized in that: The invention comprises the following components by weight: 13-18 parts by weight of acrylic resin, 5-9 parts by weight of sulfur-containing polyurethane, 2-6 parts by weight of fluorine-modified sulfaguanidine, 1-2 parts by weight of epoxy nano-silica, 3-5 parts by weight of polyvinyl pyrrolidone, 2-4 parts by weight of glycerol, and 10-12 parts by weight of deionized water; The preparation method of the sulfur-containing polyurethane is: (1) adding sulfaguanidine to anhydrous ethanol solvent, stirring and mixing, heating to 70-90°C to completely dissolve it, then continuing to add p-dimethylaminobenzaldehyde, stirring and reacting for 10-15 hours, then adding 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, stirring and reacting at 75-85°C for 6-10 hours, and washing with anhydrous ethanol and deionized water 2-3 times each after completion, and drying to obtain modified sulfaguanidine; (2) adding modified sulfaguanidine and 3-chloropropylene to N,N-dimethylformamide solvent, stirring and dissolving, and carrying out quaternization reaction at 60-80° C. for 7-15 hours. After the reaction, distilling under reduced pressure, washing and drying are performed to obtain alkenyl-modified sulfaguanidine; (3) Add 2-aminoethanethiol, alkenyl-modified sulfaguanidine and dimethylphenylphosphine to the dimethyl sulfoxide solvent, stir and mix, introduce nitrogen protection, heat to 65-85°C, apply mechanical stirring at 115-120 rpm, 300-310 W / m 2 UV irradiation, stirring and reacting for 2-5 hours, after completion, vacuum rotary evaporation to remove the solvent, washing, and drying to obtain a quaternary ammonium salt chain extender; (4) After removing water from the polyether diol, mix it evenly with hexamethylene diisocyanate, introduce nitrogen, then add dibutyltin dilaurate as a catalyst dropwise, react at 50-75°C for 3-5 hours to carry out prepolymerization, then add a quaternary ammonium salt chain extender, stir to continue the chain extension reaction, react at 40-70°C for 2-3 hours, and after the reaction is completed, cool and discharge to obtain a sulfur-containing polyurethane.

2. The solid glue for mirrors according to claim 1, characterized in that: The mass ratio of sulfaguanidine, p-dimethylaminobenzaldehyde and 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide in (1) is 1:1.6-3.4:1.3-1.

8.

3. The solid glue for mirrors according to claim 1, characterized in that: The mass ratio of modified sulfaguanidine to 3-chloropropylene in (2) is 0.4-0.6:

1.

4. The solid glue for mirrors according to claim 1, characterized in that: The mass ratio of 2-aminoethanethiol, alkenyl-modified sulfaguanidine and dimethylphenylphosphine in (3) is 2.3-2.7:1:0.01-0.

03.

5. The solid glue for mirror according to claim 1, characterized in that: The mass ratio of the polyether diol after dehydration, hexamethylene diisocyanate, dibutyltin dilaurate catalyst and quaternary ammonium salt chain extender in (4) is 1.1-2.3:1:0.01-0.03:0.4-0.

6.

6. The solid glue for mirrors according to claim 1, characterized in that: The preparation method of the fluorine-modified sulfaguanidine comprises: adding perfluorooctanoyl chloride and a quaternary ammonium salt chain extender into a tetrahydrofuran solvent, then continuously adding a triethylamine catalyst thereto, reacting at 75-100° C. for 4-6 hours, and after the reaction is completed, removing the solvent by reduced pressure distillation, washing, and recrystallizing to obtain the fluorine-modified sulfaguanidine.

7. The solid glue for mirrors according to claim 6, characterized in that: The mass ratio of the perfluorooctanoyl chloride, the quaternary ammonium salt chain extender and the triethylamine catalyst is 0.4-0.51:1:0.02-0.

03.

8. A method for preparing a solid glue for use in mirrors according to any one of claims 1 to 7, characterized in that: The preparation method of the solid glue applied to the mirror comprises: adding acrylic resin, sulfur-containing polyurethane, fluorine-modified sulfaguanidine, epoxy nano-silica, polyvinyl pyrrolidone, glycerol and deionized water into a stirrer, stirring at 60-75° C. for 10-15 minutes to obtain the solid glue applied to the mirror.

Citation Information

Patent Citations

  • Decorative anticorrosive coating material for concrete structure and construction process of decorative anticorrosive coating material

    CN118271925A

  • Electronic glue containing modified butadiene rubber and preparation method thereof

    CN118652649A

  • Paint containing wormlike nano silicon dioxide particles and preparation process thereof

    CN118813130A

  • Electronic glue containing n-hexane and preparation method thereof

    CN118956323A